Portfolio Composition and Home Ownership Importance for the Wealth Distribution in Europe - Bielskis, Karolis (Organizations and Markets in Emerging Economies, 2023)
The paper analyzes household portfolio dynamics in Europe, focusing on the period from 2010 to 2017 using data from the European Central Bank’s Household Finance and Consumption Survey (HFCS). The study examines the evolution of household portfolios after the 2008 financial crisis, with housing assets found to be one of the key drivers. On the aggregate level, the household portfolio remained stable between 2010 and 2017. Housing importance remained crucial during all the time and drove the majority of portfolio performance for households in 40–99 percentiles of the wealth distribution. With the evolution of household portfolios, age cohorts 45–54, 65 and older strengthen their positions by increasing the share of their owned assets in comparison to other age cohorts, which lost part of their shares. I conclude the paper with some stylized facts showing the relationship between home ownership, the share of portfolio in housing assets and wealth inequality between countries. The stylized facts provide evidence that household portfolios significantly concentrated in housing assets during the analyzed decade. Furthermore, the transition of households from renters to home owners contributed significantly to the changes in wealth inequality that occurred after the 2008 financial crisis.